Ніж із Володимирівки - Гошко, Т.Ю. (Археологія, 2013)
Розглянуто технологію виготовлення ножа з поховання у Великому Володимирівському кургані та внесено уточнення щодо його орнаменту й форми. Причиной данного исследования послужила возникшая дискуссия по поводу датировки погребения 6 из кургана у с. Владимировка Якимовского р-на Запорожской обл. Технологический анализ и химический состав металла изделий, как известно, дают информацию, которую нельзя получить, прибегая исключительно к морфологическому анализу. Сравнение всех рисунков ножа в публикациях с исходным образцом позволило уточнить как детали орнамента, выполненного в технике гравировки, так и его форму. У ножа изначально отсутствовал упор в месте перехода черешка в лезвие и нервюры, видимость которой создавал орнамент.
Технологический анализ показал, что изделие изготовлено путем кузнечной сварки трех пластин. Швы были прокованы не тщательно и со временем расслоились на черешке и в центре ножа. Такая техника не характерна для металлообработки поздней бронзы, особенно в изготовлении ножей.
Для сравнения состава металла привлечены известные спектральные анализы металла тех культур, которые укладываются в рамки, установленные авторами предыдущих публикаций. Хотя изделие выковано из мышьяковой бронзы, по содержанию никеля и кобальта источники металла, предположительно, можно отнести к карпатотрансильванским. Результаты спектроаналитического исследования не противоречат предложенной В.В. Отрощенко датировке всего комплекса и, в частности, ножа, периодом BrD: XIV—XIII/началом XII вв. до н. э. Present research was caused by the discussion emerged about the date of burial 6 from the barrow near Volodymyrivka of yakymivka region in zaporizhzhya oblast. A technological analysis and chemical composition of metal the wares are made of, as it is known, gives information which can not be obtained from the exceptionally morphological analysis. the com- parison of all pictures of a knife in the publications to the initial specimen allowed the author to specify both the details of decorative pattern made in the technique of engraving, and the form of knife. Initially, there were no support in the knife in the place of transition of petiole in a blade and a rib, semblance of which was made by the ornament.
the technological analysis showed that the product was made by blacksmith’s welding of three plates. the guy-sutures were not carefully forged and in course of time they exfoliated on a petiole and in the knife’s centre. Such technique was not common for metal-treatment of the late Bronze Age, especially in knives production.
For the comparison of metal composition, the author used the well-known spectral analyses of metals from those cul- tures which fit into the frames defined by the previous publications’ authors. though the item is forged of arsenic bronze, based on nickel and cobalt content, the sources of metal can be presumably referred to the Carpathian-transylvanian ones. the results of spectral analytical research do not contradict to the dating of the whole assemblage, and the knife in particular, by the period BrD from the 14th—13th c. to the beginning of the 12th c. BC, proposed by V.V. Оtroshchenko.